2010
DOI: 10.1002/adfm.201000575
|View full text |Cite
|
Sign up to set email alerts
|

Porous Silicon‐Based Optical Microsensors for Volatile Organic Analytes: Effect of Surface Chemistry on Stability and Specificity

Abstract: Sensing of the volatile organic compounds (VOCs) isopropyl alcohol (IPA) and heptane in air using sub-millimeter porous silicon-based sensor elements is demonstrated in the concentration range 50-800 ppm. The sensor elements are prepared as one-dimensional photonic crystals (rugate fi lters) by programmed electrochemical etch of p + + silicon, and analyte sensing is achieved by measurement of the wavelength shift of the photonic resonance. The sensors are studied as a function of surface chemistry: ozone oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 100 publications
(87 citation statements)
references
References 47 publications
3
83
0
Order By: Relevance
“…2b) thereby showing that the carbonized surface retains sufficient optical transparency to allow optical biosensing. Although thermal carbonization can leave black, optically dense carbonaceous deposits that completely obscure the optical interference spectrum, prior studies have shown that when the reaction is carried out at moderate temperatures (500 °C, as in the present study) the deposit is sufficiently thin to yield adequate optical transparency while retaining the desired chemical stability of a silicon carbide-like surface 23,56…”
Section: Resultsmentioning
confidence: 59%
“…2b) thereby showing that the carbonized surface retains sufficient optical transparency to allow optical biosensing. Although thermal carbonization can leave black, optically dense carbonaceous deposits that completely obscure the optical interference spectrum, prior studies have shown that when the reaction is carried out at moderate temperatures (500 °C, as in the present study) the deposit is sufficiently thin to yield adequate optical transparency while retaining the desired chemical stability of a silicon carbide-like surface 23,56…”
Section: Resultsmentioning
confidence: 59%
“…[33][34][35] In addition, the surface chemistry of PSi can be modified easily. [36][37][38] Among the different surface chemistries, thermally carbonized PSi displays a highly increased electrical conductivity, 39,40 which enables, along with the possibility of fabricating nano-and microparticles, the preparation of PSi-based solution-processable inks needed for making printable devices. In the current study, the feasibility of PSi particles for printed humidity sensor production is explored.…”
mentioning
confidence: 99%
“…The ability of the double-stack structure to discriminate water vapor and VOCs was quantified for four different VOCs: toluene, dimethyl methylphosphonate (DMMP), heptane and ethanol over a range of RH values (25% < RH < 75%). They also designed an optical microsensor by attaching the porous Si layer to the distal end of optical fibers [30]. In this work, they combined surface chemistries, such as ozone oxidation, thermal oxidation, hydrosilylation (1-dodecene), electrochemical methylation, reaction with dicholorodimethylsilane and thermal carbonization with acetylene, to modify materials.…”
Section: Sensing Of Volatile Organic Compoundsmentioning
confidence: 99%